Copper thiocyanato complexes and cocaine – a case of 'black cocaine'. Issue 1 (22nd April 2014) - Laussmann, Tim; Grzesiak, Ireneus; Krest, Alexander; Stirnat, Kathrin; Meier‐Giebing, Sigrid; Ruschewitz, Uwe; Klein, Axel
<x xml:space="preserve">Abstract</x> The chemical composition of a black powder confiscated by German customs was elucidated. Black powders are occasionally used as a 'transporter' for cocaine and are obviously especially designed to cloak the presence of the drug. The material consisting of cocaine, copper, iron, thiocyanate, and graphite was approached by analytical tools and chemical modelling. Graphite is added to the material probably with the intention of masking the typical infrared (IR) fingerprints of cocaine and can be clearly detected by powder X‐ray diffraction (XRD) and Raman spectroscopy. Cu2+ and NCS− ions, when carefully reacted with cocaine hydrochloride, form the novel compound (CocH)2[Cu(NCS)4] (CocH+ = protonated cocaine), which has been characterised by single crystal XRD, IR, NMR, UV/Vis absorption and EPR spectroscopy. Based on some further experiments the assumed composition of the original black powder is discussed. Copyright © 2014 John Wiley & Sons, Ltd.